Republic of Armenia : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper analyzes scope for further de-dollarization policies in Armenia. High financial dollarization makes Armenia more vulnerable to external shocks and limits its capacity to respond. The de-dollarization strategy is broad and comprehensive, and has achieved a reduction of deposit dollarization during the past few years. Additional efforts should focus on reducing inflation volatility and external imbalances, using prudential regulations to increase foreign currency liquidity in the banking system, and strengthening the monitoring of currency mismatches. International experience suggests, however, that further reductions in dollarization are likely to occur only gradually.